 My Math Forum In one Variable; Using Mean Value Theorem to show inequality with another unknown
 User Name Remember Me? Password

 Calculus Calculus Math Forum

 December 18th, 2016, 04:01 AM #1 Newbie   Joined: Dec 2016 From: Sweden Posts: 13 Thanks: 1 In one Variable; Using Mean Value Theorem to show inequality with another unknown I can't understand the steps in this proof. Using the Mean Value Theorem: $\displaystyle Let \: r>1 \: . \: If \: x>0 \: or \: -1 \leq \: x \: <0.$ Show that $\displaystyle (1+x)^{r}>1+rx \:$ Please help me understand the steps in the proof. I don't understand them; $\displaystyle Let \: f(x)=(1+x)^{r}-1-rx \: where \: r>1.$ $\displaystyle Then \: f'(x)=(1+x)^{r-1}-r \:$ $\displaystyle If \: -1 \leq x < 0 \: then \: f'(x)<0; \: if \: x>0, \: then \: f'(x)>0.$ $\displaystyle Thus \: f(x)>f(0)=0 \: if \: -1 \leq x < 0 \: or \: x>0.$ $\displaystyle Thus \: (1+x)^{r}>1+rx \: if \: -1 \leq x < 0 \: or \: x>0.$ This is supposed to complete it. But I do not understand a single line of it. Stuck all summer with it. Please help. Last edited by Luciferis; December 18th, 2016 at 04:08 AM. December 18th, 2016, 04:38 AM #2 Senior Member   Joined: Sep 2015 From: USA Posts: 2,370 Thanks: 1274 $f(x) = (1+x)^r - (1+r x)$ There should be no confusion about this line. They are simply defining $f$ as the difference of the terms involved in the inequality. Eventually I imagine it will be shown $f$ is non-negative. $f^\prime(x) = r(1+x)^{r-1} - r$ This is a straightforward derivative. No reason for confusion here. $-1 \leq x < 0 \Rightarrow f^\prime(x) < 0$ else $0 \leq x \Rightarrow f^\prime(x) > 0$ The second of these should be pretty clear. For the first note that $(1+x) < 1,~-1\leq x < 0 \Rightarrow (1+x)^{r-1} < 1 \Rightarrow r(1+x)^{r-1} - r = r((1+x)^{r-1}-1) < 0$ and also note that $f(0) = 1-1=0$ So for $0 < x$ we have that $f(x)$ increases from $0$ and thus $f(x)>0,~x>0$ For $-1\leq x < 0$ we have $f(x)$ decreases towards $0$ Well that must mean that it's decreasing from something greater than 0, so $f(x) > 0,~-1 \leq x < 0$ and if $f(x) > 0, ~x\neq 0$ then $(1+x)^r > 1+r x,~x \in [-1,0) \cup (0, \infty)$ Last edited by romsek; December 18th, 2016 at 04:41 AM. December 18th, 2016, 06:13 AM   #3
Newbie

Joined: Dec 2016
From: Sweden

Posts: 13
Thanks: 1

Quote:
 Originally Posted by romsek $f(x) = (1+x)^r - (1+r x)$ There should be no confusion about this line. They are simply defining $f$ as the difference of the terms involved in the inequality. Eventually I imagine it will be shown $f$ is non-negative. $f^\prime(x) = r(1+x)^{r-1} - r$ This is a straightforward derivative. No reason for confusion here. $-1 \leq x < 0 \Rightarrow f^\prime(x) < 0$ else $0 \leq x \Rightarrow f^\prime(x) > 0$ The second of these should be pretty clear. For the first note that $(1+x) < 1,~-1\leq x < 0 \Rightarrow (1+x)^{r-1} < 1 \Rightarrow r(1+x)^{r-1} - r = r((1+x)^{r-1}-1) < 0$ and also note that $f(0) = 1-1=0$ So for $0 < x$ we have that $f(x)$ increases from $0$ and thus $f(x)>0,~x>0$ For $-1\leq x < 0$ we have $f(x)$ decreases towards $0$ Well that must mean that it's decreasing from something greater than 0, so $f(x) > 0,~-1 \leq x < 0$ and if $f(x) > 0, ~x\neq 0$ then $(1+x)^r > 1+r x,~x \in [-1,0) \cup (0, \infty)$
Flawless 😀

Thank you.

Merry Christmas!!!! Tags inequality, show, theorem, unknown, variable Thread Tools Show Printable Version Email this Page Display Modes Linear Mode Switch to Hybrid Mode Switch to Threaded Mode Similar Threads Thread Thread Starter Forum Replies Last Post Luciferis Calculus 2 December 17th, 2016 08:34 PM darkflute Linear Algebra 3 June 23rd, 2012 07:08 AM lax13 Algebra 9 October 20th, 2011 02:09 PM 450081592 Calculus 1 October 5th, 2010 11:22 PM mikeportnoy Algebra 2 January 12th, 2009 11:15 AM

 Contact - Home - Forums - Cryptocurrency Forum - Top      